Effectiveness of chemical treatment of oil palm empty fruit bunch fiber as reinforcement in foamed mortar / Nur Nabilah Mohamad Bakhtiar and Md Azree Othuman Mydin - Mohamad Bakhtiar, Nur Nabilah; Mydin, Md Azree Othuman (2018)
These days, construction material manufacturers in Malaysia have put an effort to utilize industrial waste in the production of building materials especially concrete based products. It should be pointed out that natural fibers have become attention-grabbing and interesting to be employed as an industrial and structural material for restoring of structures. Nonetheless, these natural fibers which are available in large quantities in Malaysia have certain issues in attaining the anticipated engineering and durability properties particularly concerning the interface connections with the cement matrix. Hence, chemical treatment is essential to improve the matrix to filler adhesion, consequently refining its overall properties. In this study, oil palm empty fruit bunch (EFB) fiber was studied for use as reinforcement materials for cementitious composites in foamed mortar. The effect of fiber chemical treatment (2%-10% wt. sodium hydroxide chemical treatment) on durability and engineering properties of EFB fiber reinforced foamed concrete was investigated expansively. The test results show that treatment of the EFB fibers modifies the fibers interface sufficiently triggering a variation in the durability and engineering properties. Above all, 6% sodium hydroxide chemical treatment of EFB fiber offered excellent compressive and bending strength hence it's considered a better treatment concentration value in the range of 2% to 10% wt. in turn to enhance the durability and engineering properties of EFB reinforced foamed mortar.